Vliv uspořádání převodovky CVT na dynamiku jízdy vozidla - Koreis, Josef; Koreisová, Gabriela; Mazánek, Jan (Univerzita Pardubice, 2001)
Article describe organisation of gearboxes Hypertronic CVT and Extroid CVT (FIg. 1, 2, 3) with controlled frictional transmission with coherent gear ratio change and hydromechanic changemoment. Used simple frictional transmission has not reserve motion ability (Fig. 5) and then car accelerating by force of gear ratio change is unable. To enable fluent car accelerating classical gearboxes CVT contain hydrodynamic changer before controlled frictional transmission. Hydrodynamic changer solves car acceleration, but not reverse motion of car. To create reverse motion gearbox Extroid contain, (sun and planet reversing reducer), between hydrodynamic changer and frictional transmission. (Fig. 2). Simple frictional transmission has maximum gear ratio to fast. Output of controlled frictional transmission contains decelerating reducer to be maximum gear ratio of gearbox CVT unitary. (Fig. 2, 4). Hydrodynamic changer in gearboxes CVT deteriorates driving attributes of car at starting and at overtaking slowly car to the acclivity. Inconvenient attributes of serial wiring of hydrodynamic changer and simple frictional transmission can eliminate wiring of frictional transmission to branched flow system with distribution differential at output. (Fig. 9). So come into existence differntial controlled frictional transmission (DRTP) with reverse motion ability and ability to realise controlled starting of car. Examples of configuration DRTP are at pict. 10, 11, 12. Comparing of static moment qualifications of classical gearbox CVT and gearbox DRTP is at pict. 13. Gearboxes CVT with hydrodynamic changer oppress engine at starting according to pump qualification of changer. Gearbox DRTP controlled moment oppresses engine. Controlled oppress moment behaviour is arbitrary workable, for example according to optimal oppress qualification of engine. (L3). Fig. 15 contains oppress qualification of DRTP and parabolic oppress qualification of hydrodynamic changer CVT. Fig. 16. Driving moment at input DRTP grows faster. Time behaviour of speed at overtaking to the acclivity is compared ad Fig. 18. Car with gearbox DRTP has better dynamic of motion. Fig. 19 contains trajectory at overtaking to the acclivity. Fig. 20 contains car speed behaviour at accelerating at plain. Car with gearbox DRTP actives speed 100 km/h in 4,8 sec, and car with gearbox CVT hydrodynamic gear 7,5 sec.
Keywords: dynamika jízdy; vozidla; převodovka; uspořádání